A comparative study on the energy consumption of Progressive Web Apps. Issue 108 (September 2022) - Huber, Stefan; Demetz, Lukas; Felderer, Michael
Abstract: Progressive Web Apps (PWAs) are a promising approach for developing mobile apps, especially when developing apps for multiple mobile systems. As mobile devices are limited with respect to battery capacity, developers should keep the energy footprint of a mobile app as low as possible. The goal of this study is to analyze the difference in energy consumption of PWAs compared to other mobile development approaches. As mobile apps are primarily interactive in nature, we focus on UI rendering and interaction scenarios. For this, we implemented five versions of the same app with different development approaches and examined their energy footprint on two Android devices with four execution scenarios. Additionally, we extended our research by analyzing multiple real-world mobile apps to include a more practical perspective. Regarding execution environments, we also compared the energy consumption of PWAs executed in different web-browsers. The results based on sample and real-world apps show that the used development approach influences the energy footprint of a mobile app. Native development shows the lowest energy consumption. PWAs, albeit having a higher energy consumption than native apps, are a viable alternative to other mobile cross-platform development (MCPD) approaches. The experiments could not assert an inherent technological disadvantage of PWAs in contrast to other MCPD approaches when considering UI energy consumption. Moreover, the web-browser engine used to execute the PWA has a significant influence on the energy footprint of the app. Highlights: Thorough analysis of the energy consumption of sample apps and real-world apps. Progressive web apps are a viable alternative to other mobile development approaches. Web-browsers have a significant influence on the energy consumption of a PWA. Comprehensive replication package comprising accompanying research artifacts.